Ober ganzzahlige Darstellungen der Gruppe von Typus (3,3) - Matuliauskas, A.; Matuliauskienė, A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Матуляускас, М. Матуляускене. О целочисленных представлениях группы типа (3,3)A. Matuliauskas, M. Matuliauskienė. Apie (3,3) tipo grupės sveikaskaičius atvaizdavimus